Development of smoked-dried yellowfin tuna (Thunnus albacares) - Nacionales, Jeddah Serra (2000.)
The process for smoked-dried yeloowfin tuna (Thunmus albacares) was established by determining the brine concentrations and drying time that would yield the most preferred smoked-dried product under the same smoking conditions (pre-drying at 40 degree to 60 degree celsius for 30 minutes and smoking at 70 degree to 80 degree celcius for 2 1/2 hours in the Tory Kiln Mechanical Smokehouse.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tuna; Smoked fish; Smoked-dried tuna